Analisis Faktor Penyebab Ketidaklengkapan Rekam Medis Pasien Rawat Inap di Puskesmas Kotaanyar - Dian Fadilah Ayu Lestari; Indah Muflihatin (Politeknik Negeri Jember, 2020)
Based on the results of a preliminary study conducted at the Kotaanyar Public Health Center, 30 medical records of inpatients in April and May 2019 are known, which were identified based on patient identification, important reports and their authentication, the average overall number of incompleteness was 720 (53.08%). The incompleteness of the medical record has an impact which results of administrative and clinical data are not accurate, This incompleteness also creates a loss in fulfilling the patient's right to the contents of their medical record, obstruction of reporting activities and submission of claims and cause the quality of health services are low. This study aims are to analyze the factors causing incomplete medical records of inpatients, determining priority causes of problems using USG (Urgency, Seriousness, Growth) and remedial efforts are using brainstorming. This type of research uses qualitative and data collection by observation, interviews, questionnaires and documentation. The results obtained that the priority cause of the incomplete medical records problem of inpatients are there is no SOP (Standard Operational Procedure). Efforts to fix the problem are making SOP, put the SOP in the inpatient unit where it can be reached, conduct socialization at any time and renew SOP according to the SOP renewal agreement.